A simple and effective grid-supporting low voltage ride-through scheme for single-stage photovoltaic power plants. (15th January 2022) - Nasiri, Mojtaba; Arzani, Ali; McCormack, Sarah J.
Abstract: Due to the ever-increasing impact of grid-connected photovoltaic power plants (GCPPP), compliance with grid-code (GC) requirements has become inevitable. According to current GCs, not only a GCPPP needs to inject reactive current into the network with a drop in the grid's voltage, but a necessity exists to inject active power into the network during grid fault occurrence and post-faults. This is because the power system faces stability issues in the case of either GCPPP being disconnected from the network or active power not being injected into the grid after fault clearance. In this paper, a braking chopper (BC) is installed and a controller has been designed to enable fulfillment of low voltage ride through (LVRT) criteria for single-stage grid-integrated PV systems. This method proves to be simple, inexpensive, and effective for a wide range of operating conditions and different types of grid-faults. Furthermore, a current limiter has been incorporated for the DC–AC converter that is compatible with the BC controller itself. A general guideline has been devised in this research to evaluate the proposed LVRT strategy for seamless operation of single-stage GCPPPs. Not only does the GCPPP remain connected to the network by adhering to relevant GCs, but it also tracks the maximum power point after fault clearance without any delays. The simulations are carried out in MATLAB/Simulink software and comparisons have been drawn with the conventional approach. The results indicate excellent improvement in transient and steady-state operation of the GCPPP. Highlights: Simple active BC with well-rounded controller design leading to GCPPP LVRT operation enhancement. Execution of GCPPP grid-codes under both symmetrical and asymmetrical grid faults. GC-compliant PV power injection during-/post- fault disturbance under varying solar irradiance. Design of a current limiter for the DC–AC converter to confine injected current in PCC during faults. Damping of dc-link voltage second-order harmonic oscillations during asymmetrical grid faults.